IMPLEMENTATION OF COMPUTER-BASED NATIONAL ASSESSMENT (ANBK) AT SMP NEGERI 1 KETAMBE IN SOUTHEAST ACEH REGENCY - Jiwa Malem Marsya (Jurnal Penelitian Progresif, 2026)
The purpose of this study is to determine how the computer-based national assessment (ANBK) is implemented at SMP Negeri 1 Ketambe in Southeast Aceh Regency and the obstacles encountered in implementing ANBK at SMP Negeri 1 Ketambe in Southeast Aceh Regency. This study is a qualitative study conducted at SMP Negeri 1 Ketambe in Southeast Aceh Regency. The subjects in this study were the school principal and the ANBK implementation committee. The data collection techniques used in this study were observation sheets, interview guidelines, and documentation. Data analysis in this study was conducted by reducing the presentation, drawing conclusions, and validating the data. The results of this study on the implementation of the ANBK computer-based national assessment at SMP Negeri 1 Ketambe in Southeast Aceh Regency and the obstacles encountered in implementing the ANBK at SMP Negeri 1 Ketambe in Southeast Aceh Regency were seen from the analysis of research data from observations, interviews, and documentation, show that the implementation of ANBK at SMP Negeri 1 Ketambe in Southeast Aceh Regency has been carried out without any obstacles, with all implementation indicators being fulfilled, namely the AN room for students, supervisors, proctors, and technicians, the duties of supervisors, proctors, and technicians, and the rules and regulations for supervisors, proctors, and technicians, which were carried out in accordance with the predetermined steps.